Can scat analysis describe the feeding habits of big cats? A case study with jaguars (Panthera onca) in Southern Pantanal, Brazil - Perilli, Miriam L.L.; Lima, Fernando [UNESP]; Rodrigues, Flávio H.G.; Cavalcanti, Sandra M.C. (Public Library of Science (PLoS), 2016)
Large cats feeding habits have been studied through two main methods: scat analysis and the carcasses of prey killed by monitored animals. From November 2001 to April 2004, we studied jaguar predation patterns using GPS telemetry location clusters on a cattle ranch in southern Pantanal. During this period, we recorded 431 carcasses of animals preyed upon by monitored jaguars. Concurrently, we collected 125 jaguar scats opportunistically. We compared the frequencies of prey found through each method. We also compared the prey communities using Bray-Curtis similarity coefficient. These comparisons allowed us to evaluate the use of scat analysis as a means to describe jaguar feeding habits. Both approaches identified prey communities with high similarity (Bray-Curtis coefficient > 70). According to either method, jaguars consume three main prey: cattle (Bos taurus), caiman (Caiman yacare) and peccaries (Tayassu pecari and Pecari tajacu). The two methods did not differ in the frequency of the three main prey over dry and wet seasons or years sampled. Our results show that scat analysis is effective and capable of describing jaguar feeding habits.